Financial Performance and Inflation’s Effects on Indonesia’s National Private Commercial Banks’ Return on Assets - Abdul Qodir Djaelani; Ety Saraswati; Achmad Agus Priyono; Ari Kartiko (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research was conducted to investigate the effect of financial performance as represented by Loan Deposit Ratio (LDR), Non-Performing Loans (NPL), and Net Interest Margin (NIM), as well as Inflation on profitability at National Private Commercial Banks listed on the Indonesia Stock Exchange (IDX). This research adopts a quantitative approach with empirical analysis using panel data from 2017 to 2021. The sampling method uses purposive sampling, with 23 banks selected as samples. Data analysis was performed using the panel data regression method through Eviews software. The panel data estimation showed a significant influence between the Loan Funding Ratio (LFR) and Inflation variables on the Return on Assets (ROA) of national private commercial banks in Indonesia in 2017-2021. These findings provide a solid empirical basis for providing better financial policy recommendations to these banks in the future.